PENGARUH RISK, LEGAL RESERVE REQUIREMENT, DAN FIRM SIZE PADA PROFITABILITAS PERBANKAN - Paramita Handayani, I.A. Ria; Putra, I Wayan (E-Jurnal Akuntansi; Vol 14 No 2 (2016), 2016)
One of the measure of the financial performance achievement that the banks have made is the corporations’ level of profitability. This study was aimed at finding out the effect of Risk, Legal Reserve Requirement, and Firm Size on the profitability of banking corporations registered in Indonesia Stock Exchange. The sample size was 24 banking corporations registered in Indonesia Stock Exchange in the observation years from 2010 up to 2014 using purposive sampling as the sampling method. The data used were secondary data and the method of analysis used was multiple linear regression. The result of t-test showed that Deposit Risk Ratio, Legal Reserve Requirement, and Firm Size partially have a positive effect on the profitability of the banks. The result of t-test showed that Deposit Risk Ratio, Legal Reserve Requirement, and Firm Size partially have a positive effect on the profitability of the banks.
Keywords: Risk, Legal Reserve Requirement, Firm Size, ROA